Influence of cooling intensity on the structure formation in stripe steel by thermomechanical treatment - Goryany V.; Khlyntseva T.; Mamuzić I.; Radsinsky V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The results of research of microstructure of the strips from low carbon steel 45x6 and 30x8 mm in hot-rolling condition and after accelerated cooling of different intencity and schemes of the coolers movement in the cooling chambers are shown. The strengthening layer is spread unevenly along the perimeter of the rolled steel. The formation character of the structure and its spreading along the cross-section depends on intensity of cooling and the ratio of the width of the stripe to its thickness. Regimes, that provide the high level of steel’s strength with the smallest changing of the mechanical properties by the length of the rolled strip were defined.